Impact of Uterine Prolapse Surgery on Improvement of Bowel Symptoms - Zulfadli, Zulfadli (Indonesian Journal of Obstetrics and Gynecology, 2014)
Objective: To find the effectiveness of uterine prolapse surgery in patients with bowel symptoms. Method: Clinical trial without comparison study of 32 consecutive women who underwent surgery for grade III and IV uterine prolapse with bowel symptoms. Bowel symptoms score was evaluated before and three months after surgery by using the Australian Pelvic Floor Questionnaire. Data was analyzed using SPSS version 20. Result: There were significant mean differences between bowel symptoms score three months after surgery for grade III and IV uterine prolapse and before surgery although there were patients with persistent symptoms. Bowel symptoms scores include constipation, flatus incontinence, fecal incontinence, fecal urgency, defecation frequency, defecation consistency, incomplete bowel emptying, laxative use, and frequency of defecation disorder score, with p